On the Elasticity of Substitution between Labor and ICT and IP Capital and Traditional Capital - Vahagn Jerbashian (Center for Economic Studies and ifo Institute (CESifo), 2022)
I estimate CES aggregate production functions for the US, the UK, Japan, Germany, and Spain using data from the EU KLEMS database. I distinguish between three types of capital: information and communication technologies (ICT), intellectual property (IP) capital, and traditional capital. I assume that the aggregate output is produced using labor and these three types of capital and allow for differences in the elasticities of substitution between labor, an aggregate of ICT and IP capital, and traditional capital. The estimated elasticities of substitution between ICT and IP capital are strictly below one for all sample countries implying gross complementarity. ICT and IP capital together are gross substitutes for labor while traditional capital is a gross complement. The results for the US imply that the fast pace of technological progress in ICT and IP capital accumulation together are responsible for about 80 percent of the fall in labor income share.
Keywords: E22; E25; J23; O33; 330; CES production function; elasticities of substitution; system of equations; ICT; IP capital; traditional capital